Seroprevalence and Factors Associated with Canine Leishmaniasis in Baringo County, Kenya: Implications for an Integrated One Health Surveillance - Hellen Njeri Maingi; Maingi Ndichu; Richard B. Yapi; James Ng’ang’a Chege; Davis Njuguna Karanja; Bruno Enagnon Lokonon; Cherotich Jesca Tangus; Helena Ngowi; Damaris Matoke-Muhia; Bassirou Bonfoh (Veterinary Sciences, 2026)
Leishmaniasis is an emerging zoonotic disease recognized by WHO as a priority neglected tropical disease (NTD) targeted for elimination by 2030. The disease is transmitted through bites of infected female phlebotomine sand flies and presents in three main forms: cutaneous, mucocutaneous, and visceral leishmaniasis. Visceral leishmaniasis (VL) has two distinct epidemiological cycles: anthroponotic visceral leishmaniasis (AVL) cycle, caused by L. donovani and transmitted between humans, and zoonotic visceral leishmaniasis (ZVL) cycle, caused by L. infantum, with domestic dogs as the main reservoirs. ZVL represents the most severe clinical form and poses a public health risk due to a high fatality rate. In Kenya, the epidemiology and transmission dynamics of Leishmania infection among the canine population in endemic areas such as Baringo are poorly characterized. A cross-sectional epidemiological study was conducted in Baringo County, Kenya, one of the endemic foci for human visceral leishmaniasis. Blood samples were collected from 140 dogs in Rabai, Sabor, Mbechot, Kapkuikui, and Chemolingot and analyzed using Rapid Diagnostic Test (RDT) and Enzyme-linked immunosorbent assay (ELISA). Data on potential epidemiological factors and clinical status for dogs were collected using a questionnaire. Statistical analysis was performed using Pearson’s chi-square (χ2) test or Fisher’s exact test to assess associations between Leishmania seropositivity and potential risk factors. A stepwise logistic regression procedure with an entry significance level of p < 0.20 was employed to identify factors associated with leishmaniasis seroprevalence. Cohen’s kappa (κ) agreement was used to assess the diagnostic performance and accuracy of the two serological tests in the absence of a gold standard. The overall seropositivity in dogs was 7.79% and 12.14% at 95% CI for the RDT and ELISA, respectively. Multivariate analysis identified breed and clinical signs as significant factors associated with Leishmania seropositivity in dogs. Local-breed dogs were more likely to be Leishmania seropositive than mixed-breed dogs (OR = 11.92; 95% CI: 1.79–79.37; p = 0.010). Dogs without clinical signs exhibited significantly lower odds of ELISA seropositivity (OR = 0.06; 95% CI: 0.01–0.29; p < 0.001). Dogs with proper care and housing conditions had reduced risk of Leishmania seropositivity compared with poorly managed dogs. Significant association with seropositivity was observed for sex, age, origin, and reason for keeping dogs. Diagnostic evaluation showed that the RDT had an excellent specificity and Positive Predictive Value (100%), with good overall agreement with ELISA, although sensitivity was 64.7%. Hence, RDT can be a reliable alternative screening tool compared with ELISA as the reference standard. The study demonstrated the presence of Leishmania infection in the dog population in Baringo County, Kenya, a significant public health risk. Early detection and diagnosis of infections in dogs through an integrated One Health approach during routine surveillance are essential. This will facilitate treatment and/or culling of infected dogs and vector control, subsequently reducing the risk of human transmission. Hence, it will go a long way to achieving WHO’s roadmap of eliminating leishmaniasis by 2030.